Multi-hop Communication between LoRa End Devices - Triwidyastuti, Yosefine; Musayyanah, Musayyanah; Ernawati, Fifin; Affandi, Charisma Dimas (Universitas Negeri Semarang, 2020)
Gateway elimination in a LoRa network could highly reduce the network installation cost. However, LoRa end devices could not overcome many obstacles with only a point-to-point communication. Thus, this research implemented a multi-hop communication in a LoRa network. One or more LoRa end devices are placed between the source node and the destination node to act as relay nodes. A simple routing based on the packet length is configured to determine the packet transmission path. As the results, the designed multi-hop communication could improve packet success rate until 2,47 times in indoor environment. Whereas, the optimum delay time for multi-hop communication is 100 ms for each hop to produce high PRR and lowest RTT.